The Unveiling of the E-Jeepney Modernization Program Through the Lenses of the Diverse Sectors in Southern Philippines - Francesquite, Marlyn; Calva, Joy C. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Filipino passengers use Jeepneys as their primary mode of transportation in their everyday lives. However, as the world is trailing through an era of advancements, the modernization of public utility vehicles (PUV) is introduced to solve other societal problems. This study centered on the implementation, challenges, and repercussions of modernized jeepneys in the Philippines between four stakeholders involved: jeepneys operator/ driver, passenger, and implementer. The qualitative research design was utilized to gather data through key-informant interviews and archival research.The findings revealed that modernized e-jeepney positively affect the transportation system, with benefits such as reduced pollution, comfort, and job opportunities. Despite the myriad benefits associated, various stakeholders encounter significant challenges throughout its implementation, such as route rationalization, financial burden, and fierce competition.